Comparisons of Primary HIV-1 Drug Resistance between Recent and Chronic HIV-1 Infection within a Sub-Regional Cohort of Asian Patients - Sasisopin Kiertiburanakul (2018)
Background:The emergence and transmission of HIV-1 drug resistance (HIVDR) has raised concerns after rapid global antiretroviral therapy (ART) scale-up. There are limited data on the epidemiology of primary HIVDR in resource-limited settings in Asia. We aimed to determine the prevalence and compare the distribution of HIVDR in a cohort of ART-naïve Asian patients with recent and chronic HIV-1 infection.Methods:Multicenter prospective study was conducted in ART-naïve patients between 2007 and 2010. Resistance-associated mutations (RAMs) were assessed using the World Health Organization 2009 list for surveillance of primary HIVDR.Results:A total of 458 patients with recent and 1,340 patients with chronic HIV-1 infection were included in the analysis. The overall prevalence of primary HIVDR was 4.6%. Recently infected patients had a higher prevalence of primary HIVDR (6.1% vs. 4.0%, p = 0.065) and frequencies of RAMs to protease inhibitors (PIs; 3.9% vs. 1.0%, p < 0.001). Among those with recent infection, the most common RAMs to nucleoside reverse transcriptase inhibitors (NRTIs) were M184I/V and T215D/E/F/I/S/Y (1.1%), to non-NRTIs was Y181C (1.3%), and to PIs was M46I (1.5%). Of patients with chronic infection, T215D/E/F/I/S/Y (0.8%; NRTI), Y181C (0.5%; non-NRTI), and M46I (0.4%; PI) were the most common RAMs. K70R (p = 0.016) and M46I (p = 0.026) were found more frequently among recently infected patients. In multivariate logistic regression analysis in patients with chronic infection, heterosexual contact as a risk factor for HIV-1 infection was less likely to be associated with primary HIVDR compared to other risk categories (odds ratio 0.34, 95% confidence interval 0.20-0.59, p < 0.001).Conclusions:The prevalence of primary HIVDR was higher among patients with recent than chronic HIV-1 infection in our cohort, but of borderline statistical significance. Chronically infected patients with non-heterosexual risks for HIV were more likely to have primary HIVDR. © 2013 Kiertiburanakul et al.